The role of physical therapists in the early detection of skin melanoma: insights from an anonymous survey - Arouch, Bar; Elboim-Gabyzon, Michal (Frontiers in Medicine, 2024)
An anonymous online survey was conducted involving 254 Israeli physical therapists to evaluate their perspectives on their role in melanoma detection, their ability to identify suspicious skin lesions, and their patterns of referring patients for further dermatological evaluation. The results showed that while 75.2% of the physical therapists acknowledged melanoma detection as part of their professional duties, 59.1% reported insufficient knowledge in identifying suspicious lesions. Despite this, 94.1% expressed a desire to enhance their knowledge in melanoma detection. However, only 44.1% of the physical therapists actively referred patients with suspicious lesions to dermatologists. The study also identified a significant correlation between the physical therapists' professional experience and their referral rates, suggesting that increased experience might lead to more frequent referrals. This finding highlights the critical need for incorporating melanoma detection training into both physical therapy education and ongoing professional development to better equip physical therapists for early detection and referral.